How to become experienced? the practice of novice lecturer professional development at a public university - Yu, Hong; Abdullah, Arnida; Asimiran, Soaib; Muhamad, Mohd Mokhtar (Society for Research and Knowledge Management, 2021)
Novice lecturer professional development is regarded as a continuous process that begins during pre-service lecturer training and continues throughout the academic career. It is focused on enabling and empowering lecturers by improving their professional confidence, teaching skills, and classroom management. The purpose of this paper is to explore the professional development practices of novice lecturers and to comprehend their situation and feelings about these practices at a public university in China. Using a qualitative case study, five novice lecturers were selected to participate in this study. Relevant programs and activities on professional development are analyzed. Semi-structured interviews were conducted to explore the perceptions of novice lecturers. Another data collection method was documentation. The findings indicate that the professional development practices of novice lecturers in this selected university were done by organizing lecturer teaching competitions, teaching ability training, establishing the mentorship system, information technology application ability training. Novice lecturers are generally satisfied with the implementation of these programs and activities and hope that the university could provide more opportunities to help them grow quickly.